Durability evolution and associated micro-mechanisms of carbonated reactive MgO-fly ash solidified sludge from East Lake, China. (30th May 2019) - Wang, Dongxing; Xiao, Jie; He, Fujin; Zhou, Yadong
Highlights: CO2 carbonation technique is innovatively introduced in sludge reinforcement. Carbonation enhances resistance of MgO-fly ash solidified sludge to durability damage. Phase transition of magnesium carbonates occurs in water immersion & cyclic dry-wet. Durability damage induces transition between interparticle pore and interaggregate pore. Hydrated magnesium carbonates are the intrinsic mechanisms for improving durability. Abstract: The reactive MgO-fly ash blends are employed for stabilizing lacustrine sludge through absorbing gaseous CO2, which is a prospective and sustainable technique combined of carbonation and solidification. The mechanical and microstructural variation of carbonated MgO-fly ash solidified sludge subjected to three durability tests (i.e. water immersion, cyclic dry-wet, cyclic freeze–thaw) is investigated through unconfined compressive strength (UCS), X-ray diffraction (XRD), mercury intrusion porosimetry (MIP) and scanning electron microscopy (SEM) tests. The obtained results demonstrate that the CO2 carbonation reaction can greatly enhance the resistance of MgO-fly ash solidified sludge to environmental changes, and the stress–strain behaviour depends mainly on types of durability tests, damage period and carbonation mode. The main carbonation products detected in CO2 -MgO-fly ash-sludge system are the elongated prismatic hydromagnesite (skeleton constructing), flower-/bone-like and flaky dypingite and nesquehonite (pore filling and particle cementing). The coupled action of skeleton constructing-filling-cementing enables the CO2 carbonated specimens to be qualified with higher strength, better water stability, and stronger resistance to dry-wet and freeze-thaw cycles. Especially, the continuous immersion in water leads to transition of some interparticle pores into intra-aggregate pores and phase transformation of dypingite and nesquehonite to hydromagnesite. The cyclic dry-wet exposure causes partial transition of intra-aggregate pores into interparticle pores and phase transformation from dypingite and nesquehonite to hydromagnesite. However, no visible transformation between carbonation products can be recognized for specimens under freeze-thaw cycles, except an increased amount of large pores with radius around 10 μm.